Heinrich Schiller (Germany), President 1980 - 1988 - Joachim Wieler (Social Work & Society, 2008)
Thanks to the Editor of this book for the invitation to continue the series of IASSW Presidents with Prof. Dr. Heinrich Schiller, MSW. It is an honour to pay tribute to one of my role models as a social worker and social work teacher and to a friend of many years. When I ponder the title of this portrait, I have the feeling that life for one world sounds a bit like a life sentence, and that is intentional. In fact - at least to some extent - it is true. It certainly didn't always seem easy for Heinrich, and not all of his decisions were popular. But he certainly lived it and will hopefully continue "...to give us, in this world, many more impulses", as one of his biographers wrote on the occasion of his eightieth birthday. And here we are: Several quite lengthy biographies have been written about Heinrich Schiller and it would seem a little redundant to just add another one. Besides, Heinrich has written a comprehensive autobiographical life story, which I highly recommend, because what could be more interesting than his own un-manipulated account (Heinrich Schiller 1999)? But it is in German and thus not accessible to everyone who might be interested. So, my intention is to summarize from the available materials and then - since Heinrich is very much alive! - look him up and interview him for a very fresh update. So the beginning of this biographical project dates back just a little while.